Effect of informational constraints on sprint running - Tan, Ignatius Wei Ren (2019)
Nonlinear Pedagogy stems from a constraints-led approach and focuses on explaining how acquisition of coordination is learner-centered and explorative in nature. It makes use of the modification of a task’s key constraints to afford the learner to look for their own individualised solutions for the movement problem. However, one of the main challenges of using a nonlinear approach to teach new skills could be the amount of time required for exploratory learning as compared to a more linear approach. This study aims to investigate the effects of incorporating a linear pedagogical (LP) approach followed by a nonlinear pedagogical (NP) approach to train learners who are novel to sprinting in the acquisition of improved sprinting performances with reference to outcomes and gait changes. 16 adult males were recruited for this study and had to undergo 4 weeks of sprint training with either LP+NP (2 weeks+2 weeks) or only NP conditions. 40m sprint timing and gait parameters (stride length, stride frequency, ground contact time) were measured as indicators of sprint performance during pre, post and retention tests. Although slight changes in sprint performance were captured, these findings were not significant. However, it was noted that 7 participants displayed improvements in their sprint performance, indicating that more in-depth investigation could be done to further examine the presence of any possible trends or significant effects. Individual improvements suggest that future studies should be conducted to deepen the understanding of the effects of sequencing LP and NP approaches in order to develop more efficient and effective training methods.